Surface Modification of Polycarbonate by Atmospheric-Pressure Plasma Jets - Mello, Carina B. [UNESP]; Kostov, Konstantin G. [UNESP]; Machida, Munemasa; de Oliveira Hein, Luis Rogerio O. [UNESP]; de Campos, Kamila Amato [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Plasmas have been frequently employed to modify material surface properties; however, many of these processes are not suitable for treating sensitive materials and biological objects that cannot withstand vacuum and/or high temperature. Atmospheric-pressure plasma jets (APPJs) using inert gases can be easily adapted for this purpose since they exhibit high plasma stability, efficient reaction chemistry, and low temperature. In this paper, an APPJ with simple configuration was designed and applied for surface treatment of polycarbonate (PC) films. Optical emission spectroscopy was used to identify the excited plasma species presented inside the device and in the plasma plume. Material characterization was carried out by water contact angle measurements and atomic force microscopy. The interaction of the plasma jet with the PC samples resulted in a rougher surface and enhanced wettability.
Keywords: Atmospheric-pressure plasma jet (APPJ); optical emission spectra; surface modification; water contact angle (WCA)